(untitled) (Scientific journal of the Fergana State University, 2026)
The use of innovative methods and technologies in the process of primary education is important in developing students’ thinking and forming their independent learning skills. The use of digital technologies in the education of the mother tongue creates a wide opportunity for students to increase their vocabulary, to compose texts, to develop speech communication skills, and to form independent thinking and creative approaches.